Sedimentary DNA and Fossil Archives Reveal Long‐Term Phytoplankton Shifts and Their Biogeochemical Influence in a Subtropical Lake - Yu Zhao; Jianan Zheng; Meifang Zhong; Wenxiu Zheng; Bo Qin; Kexin Zhu; Chenxue Zhang; Yanjie Zhao; Enlou Zhang; Eric Capo; Rong Wang (Molecular Ecology, 2026)
Understanding long‐term phytoplankton community dynamics is essential for assessing ecological resilience and informing lake management under global change. However, centennial‐scale patterns of phytoplankton dynamics remain poorly resolved due to the limited taxonomic resolution of traditional fossil‐based paleoecological approaches. In this study, a combination of sedimentary DNA (sedDNA) and subfossil diatom analysis was used to investigate changes in the phytoplankton community over the past two centuries and associated sedimentary biogeochemical responses in Lake Xiliang, a subtropical lake in the Yangtze River Basin, China. The sedDNA data captured major shifts in both eukaryotic and cyanobacterial communities, revealing distinct ecological phases linked to human activities and regional climate warming. Under near‐natural conditions with minimal human disturbance, phytoplankton communities typically exhibit low diversity and are characterized by oligotrophic taxa such as xanthophytes and Gyrosigma . After the 1930s, increases in epiphytic Staurosira and declines in tychoplanktonic Aulacoseira suggest reduced river–lake connectivity and weaker water‐column turbulence following the construction of the Jinshui Sluice, likely facilitating macrophyte expansion. In recent decades, intensified anthropogenic pressures combined with regional warming have driven a shift toward more diverse phytoplankton assemblages enriched in cyanobacteria, reflecting elevated nutrient inputs and rising temperatures. The observed associations between phytoplankton community changes and sedimentary geochemical proxies suggest that phytoplankton dynamics may not only have responded to environmental change but also contributed to sedimentary biogeochemical cycling, particularly total organic carbon accumulation and calcium‐related processes such as photosynthesis‐induced carbonate precipitation. These findings illustrate long‐term phytoplankton community dynamics and underscore the value of sedDNA for reconstructing ecological trajectories in lake ecosystems.

Shifting patterns in tropical lake phytoplankton communities coinciding with anthropogenic nutrient and pollutant trends - Dongna Yan; Yongming Han; Patrick Rioual; Jianghu Lan; Sifan Zan; Yalan Tang; Huijia Zhang; Meiling Guo; Eric Capo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Low-oxygen freshwaters as ecological niches for mercury methylators - Anthony Kharaillah; Meifang Zhong; Júlia Dordal Soriano; Nicola Gambardella; Isabel Sanz-Sáez; Dongna Yan; Stefan Bertilsson; Erik Björn; Andrea Garcia Bravo; Eric Capo (Water Research, 2026)

Sedimentary DNA reveals phytoplankton diversity loss in a deep maar lake during the Anthropocene - Dongna Yan; Maïlys Picard; Yongming Han; Zhisheng An; Dewen Lei; Xue Zhao; Luyuan Zhang; Eric Capo (Limnology and Oceanography, 2024)
Anthropogenic‐driven environmental change, including current climate warming, has influenced lake ecosystems globally during the Anthropocene. Phytoplankton are important indicators of environmental changes in lakes and play a fundamental role in maintaining the functioning and stability of these ecosystems. However, the extent to which lake phytoplankton were affected by anthropogenic or climatic forces during the Anthropocene remains unclear. Here, we investigated the 160‐yr‐long dynamics of the phytoplankton community (cyanobacteria and eukaryotic microalgae) in response to anthropogenic forcing in Sihailongwan Maar Lake—a candidate for a Global boundary Stratotype Section and Point for demarcation of the Anthropocene—using DNA metabarcoding and traditional paleolimnological approaches. Our results show a significant decline in phytoplankton diversity and an abrupt shift in community composition around the 1950s, corresponding to the beginning of the “Great Acceleration” period. Specifically, phytoplankton taxa coexistence patterns, niche differentiation, and assembly mechanisms changed significantly after the 1950s. Overall, increases in air temperature and anthropogenic forcing appear to be the dominant controls for community reorganization and diversity decline of the phytoplankton from this deep maar lake. A neutral community model suggests that phytoplankton community composition was mainly controlled by stochastic processes before the 1950s; however, as time progressed, deterministic effects driven by anthropogenic global warming increased. The results of this study imply that anthropogenic perturbations have led to a loss of phytoplankton diversity and a further decline in ecological resilience in deep lakes, with likely knock‐on effects on the productivity and function of lake ecosystems.

Anthropogenic drivers accelerate the changes of lake microbial eukaryotic communities over the past 160 years - Dongna Yan; Yongming Han; Zhisheng An; Dewen Lei; Xue Zhao; Haiyan Zhao; Jinzhao Liu; Eric Capo (Quaternary Science Reviews, 2024)

Revisiting the mercury cycle in marine sediments: A potential multifaceted role for Desulfobacterota - Blanca Rincón-Tomás; Anders Lanzén; Pablo Sánchez; Mónica Estupiñán; Isabel Sanz-Sáez; M. Elisabete Bilbao; Diana Rojo; Iñaki Mendibil; Carla Pérez-Cruz; Marta Ferri; Eric Capo; Ion L. Abad-Recio; et al. (Journal of Hazardous Materials, 2024)

Environmental filtering governs consistent vertical zonation in sedimentary microbial communities across disconnected mountain lakes - Jordan M. Von Eggers; Nathan I. Wisnoski; John W. Calder; Eric Capo; Dulcinea V. Groff; Amy C. Krist; Bryan Shuman (Environmental Microbiology, 2024)
Subsurface microorganisms make up the majority of Earth's microbial biomass, but ecological processes governing surface communities may not explain community patterns at depth because of burial. Depth constrains dispersal and energy availability, and when combined with geographic isolation across landscapes, may influence community assembly. We sequenced the 16S rRNA gene of bacteria and archaea from 48 sediment cores across 36 lakes in four disconnected mountain ranges in Wyoming, USA and used null models to infer assembly processes across depth, spatial isolation, and varying environments. Although we expected strong dispersal limitations across these isolated settings, community composition was primarily shaped by environmental selection. Communities consistently shifted from domination by organisms that degrade organic matter at the surface to methanogenic, low‐energy adapted taxa in deeper zones. Stochastic processes—like dispersal limitation—contributed to differences among lakes, but because these effects weakened with depth, selection processes ultimately governed subsurface microbial biogeography.

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

Characterization of lacustrine harmful algal blooms using multiple biomarkers: Historical processes, driving synergy, and ecological shifts - Qi Lin; Ke Zhang; Suzanne McGowan; Shixin Huang; Qingju Xue; Eric Capo; Can Zhang; Cheng Zhao; Ji Shen (Water Research, 2023)

Anaerobic mercury methylators inhabit sinking particles of oxic water columns - Eric Capo; Claudia Cosio; Elena Gascón Díez; Jean-Luc Loizeau; Elsa Mendes; Thierry Adatte; Sören Franzenburg; Andrea G. Bravo (Water Research, 2023)

Environmental paleomicrobiology: using DNA preserved in aquatic sediments to its full potential - Eric Capo; Marie‐Eve Monchamp; Marco J. L. Coolen; Isabelle Domaizon; Linda Armbrecht; Stefan Bertilsson (Environmental Microbiology, 2022)
Summary In‐depth knowledge about spatial and temporal variation in microbial diversity and function is needed for a better understanding of ecological and evolutionary responses to global change. In particular, the study of microbial ancient DNA preserved in sediment archives from lakes and oceans can help us to evaluate the responses of aquatic microbes in the past and make predictions about future biodiversity change in those ecosystems. Recent advances in molecular genetic methods applied to the analysis of historically deposited DNA in sediments have not only allowed the taxonomic identification of past aquatic microbial communities but also enabled tracing their evolution and adaptation to episodic disturbances and gradual environmental change. Nevertheless, some challenges remain for scientists to take full advantage of the rapidly developing field of paleo‐genetics, including the limited ability to detect rare taxa and reconstruct complete genomes for evolutionary studies. Here, we provide a brief review of some of the recent advances in the field of environmental paleomicrobiology and discuss remaining challenges related to the application of molecular genetic methods to study microbial diversity, ecology, and evolution in sediment archives. We anticipate that, in the near future, environmental paleomicrobiology will shed new light on the processes of microbial genome evolution and microbial ecosystem responses to quaternary environmental changes at an unprecedented level of detail. This information can, for example, aid geological reconstructions of biogeochemical cycles and predict ecosystem responses to environmental perturbations, including in the context of human‐induced global changes.

Oxygen‐deficient water zones in the Baltic Sea promote uncharacterized Hg methylating microorganisms in underlying sediments - Eric Capo; Elias Broman; Stefano Bonaglia; Andrea G. Bravo; Stefan Bertilsson; Anne L. Soerensen; Jarone Pinhassi; Daniel Lundin; Moritz Buck; Per O. J. Hall; Francisco J. A. Nascimento; Erik Björn (Limnology and Oceanography, 2022)
Human‐induced expansion of oxygen‐deficient zones can have dramatic impacts on marine systems and its resident biota. One example is the formation of the potent neurotoxic methylmercury (MeHg) that is mediated by microbial methylation of inorganic divalent Hg (Hg II ) under oxygen‐deficient conditions. A negative consequence of the expansion of oxygen‐deficient zones could be an increase in MeHg production due to shifts in microbial communities in favor of microorganisms methylating Hg. There is, however, limited knowledge about Hg‐methylating microbes, i.e., those carrying hgc genes critical for mediating the process, from marine sediments. Here, we aim to study the presence of hgc genes and transcripts in metagenomes and metatranscriptomes from four surface sediments with contrasting concentrations of oxygen and sulfide in the Baltic Sea. We show that potential Hg methylators differed among sediments depending on redox conditions. Sediments with an oxygenated surface featured hgc ‐like genes and transcripts predominantly associated with uncultured Desulfobacterota (OalgD group) and Desulfobacterales (including Desulfobacula sp.) while sediments with a hypoxic‐anoxic surface included hgc ‐carrying Verrucomicrobia, unclassified Desulfobacterales, Desulfatiglandales, and uncharacterized microbes. Our data suggest that the expansion of oxygen‐deficient zones in marine systems may lead to a compositional change of Hg‐methylating microbial groups in the sediments, where Hg methylators whose metabolism and biology have not yet been characterized will be promoted and expand.

Synergistic impacts of nutrient enrichment and climate change on long‐term water quality and ecological dynamics in contrasting shallow‐lake zones - Qi Lin; Ke Zhang; Suzanne McGowan; Eric Capo; Ji Shen (Limnology and Oceanography, 2021)
Anthropogenic and climatic stressors on freshwater ecosystems are of global concern. However, the interactions and effects of multiple stressors (e.g., nutrient enrichment, climate warming, altered wind and precipitation) acting over different spatial and temporal scales are often complex and remain controversial. Here, we reconstructed one‐century dynamics of eutrophication and primary producer communities in algal‐dominated and macrophyte‐dominated zones of a large shallow lake (Taihu, China), by integrating sedimentary photosynthetic pigments and geochemical records with water monitoring and historical archives. We aimed to explore the long‐term underlying mechanisms of the responses of water quality and lake biota to multiple environmental perturbations. We found that water quality degradation and algal community modification showed similar trends but distinct timings and trajectories in contrasting ecological zones. Onset and intensity of eutrophication in north Meiliang Bay (since the 1950s) exceeded far beyond that of macrophyte‐dominated Eastern Taihu (~1990s). Anthropogenic nutrients overtook past climatic control on production and composition of phototrophic assemblages. More importantly, lake phytoplankton responded markedly to climate warming, decreasing wind speed, and extreme weathers after cultural eutrophication. Synergistic interactions of nutrients and climate on lake ecosystems became increasingly significant in promoting harmful algal blooms (HABs) dominated by Microcystis , close to the hyper‐eutrophic north lake zones. The asynchronous limnological and ecological responses also indicated the modulating roles of lake ecological regime and catchment hydrogeomorphic characteristic. Collectively, our findings suggest that mitigation of eutrophication and HABs calls for a triple management strategy integrating anthropogenic nutrients, climate change, and lake‐catchment setting.

Terrestrial dissolved organic matter inflow drives temporal dynamics of the bacterial community of a subarctic estuary (northern Baltic Sea) - Daniela Figueroa; Eric Capo; Markus V. Lindh; Owen F. Rowe; Joanna Paczkowska; Jarone Pinhassi; Agneta Andersson (Environmental Microbiology, 2021)
Summary Climate change is projected to cause increased inflow of terrestrial dissolved organic matter to coastal areas in northerly regions. Estuarine bacterial community will thereby receive larger loads of organic matter and inorganic nutrients available for microbial metabolism. The composition of the bacterial community and its ecological functions may thus be affected. We studied the responses of bacterial community to inflow of terrestrial dissolved organic matter in a subarctic estuary in the northern Baltic Sea, using a 16S rRNA gene metabarcoding approach. Betaproteobacteria dominated during the spring river flush, constituting ~ 60% of the bacterial community. Bacterial diversity increased as the runoff decreased during summer, when Verrucomicrobia, Betaproteobacteria, Bacteroidetes, Gammaproteobacteria and Planctomycetes dominated the community. Network analysis revealed that a larger number of associations between bacterial populations occurred during the summer than in spring. Betaproteobacteria and Bacteroidetes populations appeared to display similar correlations to environmental factors. In spring, freshly discharged organic matter favoured specialists, while in summer a mix of autochthonous and terrestrial organic matter promoted the development of generalists. Our study indicates that increased inflows of terrestrial organic matter‐loaded freshwater to coastal areas would promote specialist bacteria, which in turn might enhance the transformation of terrestrial organic matter in estuarine environments.

Anthropogenic impact on the historical phytoplankton community of Lake Constance reconstructed by multimarker analysis of sediment‐core environmental DNA - Anan Ibrahim; Eric Capo; Martin Wessels; Isabel Martin; Axel Meyer; David Schleheck; Laura S. Epp (Molecular Ecology, 2021)
During the 20th century, many lakes in the Northern Hemisphere were affected by increasing human population and urbanization along their shorelines and catchment, resulting in aquatic eutrophication. Ecosystem monitoring commenced only after the changes became apparent, precluding any examination of timing and dynamics of initial community change in the past and comparison of pre‐ and postimpact communities. Peri‐Alpine Lake Constance (Germany) underwent a mid‐century period of eutrophication followed by re‐oligotrophication since the 1980s and is now experiencing warm temperatures. We extended the period for which monitoring data of indicator organisms exist by analysing historical environmental DNA (eDNA) from a sediment core dating back some 110 years. Using three metabarcoding markers—for microbial eukaryotes, diatoms and cyanobacteria—we revealed two major breakpoints of community change, in the 1930s and the mid‐1990s. In our core, the latest response was exhibited by diatoms, which are classically used as palaeo‐bioindicators for the trophic state of lakes. Following re‐oligotrophication, overall diversity values reverted to similar ones of the early 20th century, but multivariate analysis indicated that the present community is substantially dissimilar. Community changes of all three groups were strongly correlated to phosphorus concentration changes, whereas significant relationships to temperature were only observed when we did not account for temporal autocorrelation. Our results indicate that each microbial group analysed exhibited a unique response, highlighting the particular strength of multimarker analysis of eDNA, which is not limited to organisms with visible remains and can therefore discover yet unknown responses and abiotic–biotic relationships.

To what extent is the DNA of microbial eukaryotes modified during burying into lake sediments? A repeat-coring approach on annually laminated sediments - Eric Capo; Isabelle Domaizon; Dominique Maier; Didier Debroas; Christian Bigler (Journal of Paleolimnology, 2017)

Tracking a century of changes in microbial eukaryotic diversity in lakes driven by nutrient enrichment and climate warming - Eric Capo; Didier Debroas; Fabien Arnaud; Marie‐Elodie Perga; Cécile Chardon; Isabelle Domaizon (Environmental Microbiology, 2017)
Summary High‐throughput sequencing of sedimentary DNA (sed‐DNA) was utilized to reconstruct the temporal dynamics of microbial eukaryotic communities (MECs) at a centennial scale in two re‐oligotrophicated lakes that were exposed to different levels of phosphorus enrichment. The temporal changes within the MECs were expressed in terms of richness, composition and community structure to investigate their relationships with two key forcing factors (i.e., nutrient enrichment and climate warming). Various groups, including Apicomplexa, Cercozoa, Chrysophyceae, Ciliophora, Chlorophyceae and Dinophyceae, responded to phosphorus enrichment levels with either positive or negative impacts on their richness and relative abundance. For both lakes, statistical modelling demonstrated that phosphorus concentration ([P]) was a dominant contributor to MECs modifications before the 1980s; after the mid‐80s, the contribution of air temperature changes increased and potentially surpassed the contribution of [P]. Co‐occurrence network analysis revealed that some clusters of taxa (i.e., modules) composed mainly of Dinophyceae and unclassified Alveolata were strongly correlated to air temperature in both lakes. Overall, our data showed that sed‐DNA constitutes a precious archive of information on past biodiversity changes, allowing the study of the dynamics of numerous eukaryotic groups that were not traditionally considered in paleo‐reconstructions.

DNA-based methods in paleolimnology: new opportunities for investigating long-term dynamics of lacustrine biodiversity - Isabelle Domaizon; Amanda Winegardner; Eric Capo; Joanna Gauthier; Irene Gregory-Eaves (Journal of Paleolimnology, 2017)

Long‐term dynamics in microbial eukaryotes communities: a palaeolimnological view based on sedimentary DNA - Eric Capo; Didier Debroas; Fabien Arnaud; Typhaine Guillemot; Vincent Bichet; Laurent Millet; Emilie Gauthier; Charly Massa; Anne‐Lise Develle; Cécile Pignol; Franck Lejzerowicz; Isabelle Domaizon (Molecular Ecology, 2016)
Assessing the extent to which changes in lacustrine biodiversity are affected by anthropogenic or climatic forces requires extensive palaeolimnological data. We used high‐throughput sequencing to generate time‐series data encompassing over 2200 years of microbial eukaryotes (protists and Fungi) diversity changes from the sedimentary DNA record of two lakes (Lake Bourget in French Alps and Lake Igaliku in Greenland). From 176 samples, we sequenced a large diversity of microbial eukaryotes, with a total 16 386 operational taxonomic units distributed within 50 phylogenetic groups. Thus, microbial groups, such as Chlorophyta, Dinophyceae, Haptophyceae and Ciliophora, that were not previously considered in lacustrine sediment record analyses appeared to be potential biological markers of trophic status changes. Our data suggest that shifts in relative abundance of extant species, including shifts between rare and abundant taxa, drive ecosystem responses to local and global environmental changes. Community structure shift events were concomitant with major climate variations (more particularly in Lake Igaliku). However, this study shows that the impacts of climatic fluctuations may be overpassed by the high‐magnitude eutrophication impacts, as observed in the eutrophicated Lake Bourget. Overall, our data show that DNA preserved in sediment constitutes a precious archive of information on past biodiversity changes.